Pemetaan Pemanfaatan Alat Permainan Edukatif (APE) dalam Mengembangkan Sosial Emosional Anak Usia Dini di Gugus III Kecamatan Batukliang Tahun 2021 - Sri Endang Harviani Nur; Baik Nilawati Astini; Nurhasanah Nurhasanah; Ika Rachmayani (Indonesian Journal of Elementary and Childhood Education, 2021)
The purpose of this study is to find out mapping the utilization of APE in developing social emotional in Group III of Batukliang Subdistrict in 2021. This type of research is survey research. The subject of this study is all teachers who teach in kindergarten / PAUD in group III numbering 30 teachers. The data collection methods used in this study are observation, interview and documentation methods. The data that has been collected is then analyzed descriptively quantitatively. Based on data obtained educational game tools that are widely used or used by teachers for stimulation of social emotional development, namely 15 APE including Beams, Playdogs, congklak, clogs, role playing tools, ropes / rubber, jungka-jungkit, prosotan, rotary bowls, swings, titian boards, compound stairs, basket balls, large mazes, and ladder snakes and APE are dominantly used with a duration of use time of 30 minutes, it is used in core activities and with highly viable APE states such as APE Beams, playdogs and Role Play Tools (85%). Utilization of large APE mazes is still rarely used in the learning process (50%). APE that is worth using such as APE swing, prosotan, rope / rubber, snake ladder, beam, playdog, congklak and role playing equipment gained a percentage of 85%. APE such as snake ladders, large mazes, compound stairs and jungka jungka are not suitable for use because the circumstances are no longer possible for use in the process of defense (18%).